SISTEM PERHITUNGAN LAMA PENYINARAN MATAHARI DENGAN METODE OTSU THRESHOLD (STUDI KASUS: ST. KLIMATOLOGI BARONGAN) - Pujiastuti, Asih; Harjoko, Agus (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2016)
Solar radiation measurements in climatology station barongan done by using campbell stokes and record card. Solar radiation is the accumulation of the whole length of the object radiation recorded on the record card. Solar radiation data reading performed by observers by estimating the long of object irradiation compared with the scale of hours listed on the record card. The difficulties encountered by observers in conducting solar radiation data readout is the shape of the object radiation recorded on the record card are not always in the form of elongated areas, some areas disjointed, even can only form small holes along the track on the card record. The purpose of this study was to design and build a system that can be used to calculate solar radiation recorded on the card record, thus increasing the accuracy of measurement data readout. Cropping process is carried out in order to obtain the right area for analysis. The approach method in object segmentation is done by implementing a solar radiation threshold otsu method. The test results showed that the determination o f the radius o f the opening and removing noise value appropriately irradiation can obtain the number o f objects on test images with RMSEof1.4429 compared with the amount o f exposure o f the image o f the original object. Results o f calculation solar radiation by the system showed system RMSE o f 0,51 to observer calculation.